PENINGKATAN HASIL BELAJAR SISWA TENTANG LUAS BANGUN DATAR SEGI BANYAK DENGAN MEDIA KENA (KERTAS WARNA) - YANI SURYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study starts from the problem of the number of students who feel lazy to learn mathematics because they have difficulty in calculating, especially determining the area of ??a polygon. Through the medium of color paper, calculating the area of ??a polygon becomes very easy and the possibility of experiencing errors is very small. The purpose of this research is to examine the effectiveness of